O lazer como direito fundamental : problemas de justificação e garantia - Costa Neto, Antônio Cavalcante da (2010)
This work examines the theme of the fundamental right to leisure. Starting from the historical perspective in Brazil and worldwide, its conceptual definition and relation to other spheres of social organization, leisure is studied in the context of human rights and citizenship, in order to identify the main problems related to its justification and assurance. The study seeks to demonstrate that the question of justification is related to the lack of clarity in understanding the concept of leisure, sometimes associated with the negative idea of idleness, characteristic of the ideology of exaltation of work, as well as the trend of alienation of leisure, in the so-called consumer society. The discussion on the issue of security, in turn, takes into account the concepts of ―existential minimum‖ and ―reservation of possibility‖, and examines the difficulties in implementation of public policies for leisure, especially for social minorities. In particular, we have studied the economic obstacles, social and cultural dimensions to guarantee women's right to leisure. The dissertation also emphasizes the importance of education for leisure as part of education for human rights in order to create an ethic of free time, taking into account that the mere inclusion of leisure among the fundamental rights provided in the Constitution does not a sufficient condition for effectiveness and universality of this right.